The acquisition of the clitic ci among typically developing Italian preschoolers: preliminary data - Suozzi, Alice; Gagliardi, Gloria (Linguistik Online, 2022)
This paper explores the acquisitional patterns of the Italian ci morpheme and its potential role as a clinical marker for Developmental Language Disorder (DLD) in Italian-speaking children, taking into account its distributional, sociolinguistic, and typological properties. To this purpose, we (i) administered a test for the elicited production of clitic pronouns in Italian – which we will refer to as “T-PEC” in the following – to 126 school-aged Italian speakers and (ii) developed a novel test focused on the ci morpheme in order to investigate its production by five-year-old typically developing children. The results and their theoretical interpretations are of particular interest since they could shed light on the acquisition of the morpheme, thus helping understand both typical and atypical grammar development. Given the continuity of the two, it could also be applied to the diagnosis and rehabilitation of DLD, which remains a major challenge for child neuropsychiatrists, psychologists, and speech-language therapists.